Junky - Deza, Fonz.; Gonzales, Marilou C.; Tolentino, Leah. ([Manila] Asian Social Institute, 1992)
Reveals the truth about junk foods, cola drinks and addictive beverages.
Keywords: Junk food; Beverages; Caffeine -- Physiological effect; Health science